Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.4091
|View full text |Cite
|
Sign up to set email alerts
|

THU0385 Assessment of relationship between beliefs' about medicines and treatment adherence in ankylosing spondylitis patients

Abstract: BackgroundAnkylosing spondylitis (AS) is a chronic disease requiring long-term treatment. Patients' beliefs about medicines and treatment may affect their treatment adherence and treatment success.ObjectivesIn this study, we aimed to investigate the relationship between beliefs about medicines and treatment adherence in AS patients.MethodsThis cross-sectional study was conducted in a single tertiary rheumatology clinic. One hundred and fifty three AS patients were enrolled to the study. Socio-demographic and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another study of patients with AS in Turkey found that the medication adherence rate was 36.6%. 7 Studies of patients with rheumatic diseases found that medication adherence was affected by patients' sociodemographic characteristics, side effects, dosage, and type of medications, forgetfulness, and concerns about potential harmful effects of the medications on the internal organs. 5,[8][9][10][11][12] For patients with AS, lack of social support is one of the factors that influence medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Another study of patients with AS in Turkey found that the medication adherence rate was 36.6%. 7 Studies of patients with rheumatic diseases found that medication adherence was affected by patients' sociodemographic characteristics, side effects, dosage, and type of medications, forgetfulness, and concerns about potential harmful effects of the medications on the internal organs. 5,[8][9][10][11][12] For patients with AS, lack of social support is one of the factors that influence medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is an affective disorder characterized by low emotions, crying, sadness, disappointment, reduced mobility, and delayed thinking and cognitive functions (10). Anxiety refers to an inner restlessness or unfounded fear without obvious objective reasons, which is a normal emotional response when people encounter challenges, difficulties or dangers (11).…”
Section: Discussionmentioning
confidence: 99%